Bedside emergency cardiac ultrasound in children - Doniger, Stephanie J (Medknow Publications, 2010)
Bedside emergency ultrasound has rapidly developed over the past several years and has now become part of the standard of care for several applications. While it has only recently been applied to critically ill pediatric patients, several of the well-established adult indications may be applied to pediatric patients. One of the most important and life-saving applications is bedside echocardiography. While bedside emergency ultrasonography does not serve to replace formal comprehensive studies, it serves as an extension of the physical examination. It is especially useful as a rapid and effective tool in the diagnosis of pericardial effusions, tamponade and in distinguishing potentially reversible causes of pulseless electrical activity from asystole. Most recently, left ventricular function and inferior vena cava measurements have proven helpful in the assessment of undifferentiated hypotension and shock in adults and children. Future research remains to be carried out in determining the efficacy of bedside ultrasonography in pediatric-specific pathology such as congenital heart disease. This article serves as a comprehensive review of the adult literature and a review of the recent applications in the pediatric emergency department. It also highlights the techniques of bedside ultrasonography with examples of normal and pathologic images.